AHOK AND BLASPHEMY CASE IN KOMPAS AND REPUBLIKA ONLINE MEDIA: A CLASH OF IDEOLOGIES - Muhammad Beni Saputra (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2020)
Ahok's speech in Kepulauan Seribu was viral on the internet. The speech put the ethnic Chinese Christian Jakarta governorÂ into a national spotlight. Mass media then sought to interpret Ahok's speech by framing its content. Using Robert Entman's framing theory, this paper analyzes online media framing of Republika and Kompas on Ahok and a blasphemy case involving him. Content analysis of the news articles published by the two online media shows that the framing of Ahok and the blasphemy case differ in reporting and focus. KompasÂ Online mostly reported positive news about Ahok, while Republika Online demonstrated a different pattern of framing. On the blasphemy case, Kompas Online focused on defense, whereas Republika Online emphasized that Ahok had insulted Islam and had to be jailed. These differences are manifestations of an ideological clash between Kompas and Republika.